Feminisme eksistensialis dalam Film Penyalin Cahaya: Kajian sosiologi sastra - Purwaningtyas, Septa; Prawoto, Eko Cahyo (Universitas Lampung, 2023)
Film is an interesting work of art which has aspects in it, one of which is the social aspect whichrefers to feelings. Women are one aspect that is very sensitive to feelings and emotions. This understanding is feminism. This research attempts to examine how existentialist feminism is expressed in the film Photocopier. This research is descriptive and qualitative in nature and thesource of the data used in this research is a film transcript entitled “Photocopier”. The data obtained were analyzed using the theory of existentialist feminism. Data collection methods and techniques in this study used narrative methods in the form of documents, texts, or readings and writings. Methods and techniques of data analysis in this study used a qualitative descriptive method which was carried out through image descriptions and forms of existentialist feminism. This study found that transcendence can be achieved based on the four strategies applied, based on Beauvoir's theory of existentialist feminism, namely: 1. Women can work in the film Photocopier, 2. Women can become intellectuals in the film Photocopier, 3. Women achieve socialist transformation in the film Photocopier, 4. Women can reject their Otherness in the film Photocopier.Keywords: Sociology of literature, Existensial Feminism, Film